Heavy metals and mineral elements of Vernonia ambigua, Vernonia oocephala and Vernonia purpurea used in northern nigerian traditional medicine - ALIYU, Abubakar Babando; AJIBOLA, Oshanimi Jimmy; MUNTAKA, Sulaiman Mohammed; GWARZO, Umar Sani; GARBA, Zaharaddeen Nasir; OYEWALE, Adebayo Ojo (Vitae, 2015)
Background: Vernonia species are widely consumed as vegetables or medicinal herbs for the treatment of various human diseases in Nigeria. Nevertheless, there exists a growing concern for consumption safety of those herbal plants, due to increasing environmental pollution. This is because plants can accumulate some heavy metals that constitute a potential risk to human health. Nonetheless, also essential elements may be accumulated in plants, which provide nutrients for combating diseases and maintaining human health. Objectives: The purpose of the study was to analyze some heavy metals and mineral elements on Vernonia ambigua, V. oocephala and V. pupurea commonly used in Northern Nigerian traditional medicine. Methods: Atomic absorption spectrometry (AAS) was used to determine the major elements (calcium and magnesium), trace elements (iron and manganese) and heavy metals (copper, cobalt, chromium, cadmium, lead and zinc). Results: We found a high Ca and Fe content in V. ambigua, Mg and Co in V. oocephala, and Cu and Cr in V. pupurea; in contrast, the last specie, showed low accumulation of Pb and Cd among all studied species. Conclusion: This study revealed that toxic elements concentrations are lower than the allowed dietary intake (ADI) in all the three Vernonia species. The quantitative estimation of these elements is important to understanding the pharmacological and/or toxicological actions of medicinal plants for safe use.